Technical Analysis of Erection in Pilot Plant Industries at Industrial Vegetable Oil or Industrial Lauric Oil - Oetomo, Dedy Setyo (Yayasan Gema Bina Nusantara, 2024)
One source for improving the economy of the green fuel industry is to replace the conventional raw material CPO/CPKO (in this case, formerly processed into RBDPO) with the special palm oil IVO/ILO (industrial vegetable oil or lustrial linoleic oil). The technical aspects to be discussed are the selection of technology, production capacity and production plan, mass balance, production process description, technical equipment specifications, and availability of raw materials, including mechanical and electrical analysis. The abbreviation for the results of this study is that the raw material used is CPO/CPKO, and the product produced is IVO/ILO, which will be used as green fuel material. The process selected is the selection of the production process. IVO/ILO refers to the process of production of CPO, and RBDPO refers to the SNI standard or specification 8875:2020. Its production capacity is 10 tph, the TBS raw material requirement is +540–700 tons per day, and the energy requirement for wood work stations such as reception stations, thresher stations, pressing stations, clarification stations, seed processing stations, and earthquake amps stations Boiler Station and Bleaching Station reach 266.6 KW, where electricity and steam energy are obtained from fiber raw materials and palm fruit shells.